PELAKSANAAN PEMBELAJARAN BERBASIS PROYEK DALAM PENDIDIKAN SAINS: SEBUAH KAJIAN AWAL (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract Partly teachers believe that application of project based learning was hard to be done because of sosio economic factors, which is during the application of it, need equipment and material which hard to be obtained by student, whereas project based learning was suggested by Kurikulum Pendidikan Indonesia 2013. Therisetobjective is getting the declaration about necessity project based learning to be implemented by teachers in pekanbaru. Survey have been done for 32 teachers from various school around pekanbaru. The result was 56.25% teachers agree using project based learning in science study if the materials and tools available. 50% of them said too difficult getting equipment from environment around, 56,25% said difficult to prepare media for the project, and 75% said project based learning have been done before. In other side, 50% teachers earned that project based learning relatively made the student more creative and innovative and 75% believe that using project based learning made student easier to understanding the study. Based on information above can be concluded that most teachers believe project based learning is necessary to be implemented, but it need sufficient tools and materials, idea of project, the cheap cost, and the avaibility of project based learning moduleâs for teachers and teaching moduleâs for student to optimize it.Key words :science study, project based learning, science project.